KINERJA ENTITAS, KEBIJAKAN HUTANG DAN KEPEMILIKAN SAHAM TERHADAP NILAI PERUSAHAAN - Rudi Setiadi Tjahjono; Shinta Maria Magdalena (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to obtain empirical evidence regarding the effect of the independent variables consist of Company’s performances factors relating to profitability, liquidity, dividend, firm size and debt policy factor and share ownership factos relating to managerial and institutional ownership on the dependent variable of firm value. In this study, the population used were non-financial companies listed on the Indonesia Stock Exchange during 2018 to 2020. The sample used in this study which is totalled of 62 companies listed on the Indonesia Stock Exchange. Sampling in this study using purposive sampling method with a total sample of 186 data. The data analysis used is using multiple regression and the data is processed using the SPSS application. The results of this study indicate that institutional ownership, profitability, and debt policy have influence on firm value. Meanwhile, liquidity, dividend, firm size and managerial ownership have no influence on firm value.